2020
DOI: 10.1002/asia.202000037
|View full text |Cite
|
Sign up to set email alerts
|

Columnar Stacking of Partially Fluorinated [4]Helicenes: C−H⋅⋅⋅F Interactions Change the Stacking Orientation

Abstract: The partial fluorination of polycyclic aromatic hydrocarbons often produces a layered crystal packing, where fluorinated aromatic surfaces are stacked over nonfluorinated aromatic surfaces. Herein, we report the synthesis and crystal packing of partially fluorinated [4]helicenes with steric congestion resulting from H and F atoms in the fjord region. F 6 -[4]Helicene forms head-to-tail columnar stacks consisting of an alternate arrangement of perfluorinated and nonfluorinated naphthalene moieties. With decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Keeping this in mind, several modifications have been proposed in recent times ,,, aiming at improving the g -factor and Φ FL . Typical modifications are based on either substitution of hydrogens in helicenes by other atoms/groups or fusion of aromatic rings onto the helical backbone to produce ring-fused carbo­[ n ]­helicenes. Recently, Kubo et al reported dimethoxy and dicyano substituted-carbo[7]­helicenes with improved g CPL values compared to the results for parents systems. While 3.5- and 6-fold increments were obtained for Φ FL and fluorescence rate constant ( K f ), respectively, for dicyanocarbo[5]­helicene, ≥4-fold increments were obtained for the dicyano-carbo[7]­helicene .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keeping this in mind, several modifications have been proposed in recent times ,,, aiming at improving the g -factor and Φ FL . Typical modifications are based on either substitution of hydrogens in helicenes by other atoms/groups or fusion of aromatic rings onto the helical backbone to produce ring-fused carbo­[ n ]­helicenes. Recently, Kubo et al reported dimethoxy and dicyano substituted-carbo[7]­helicenes with improved g CPL values compared to the results for parents systems. While 3.5- and 6-fold increments were obtained for Φ FL and fluorescence rate constant ( K f ), respectively, for dicyanocarbo[5]­helicene, ≥4-fold increments were obtained for the dicyano-carbo[7]­helicene .…”
Section: Introductionmentioning
confidence: 99%
“…While 3.5- and 6-fold increments were obtained for Φ FL and fluorescence rate constant ( K f ), respectively, for dicyanocarbo[5]­helicene, ≥4-fold increments were obtained for the dicyano-carbo[7]­helicene . Similar to pristine carbohelicenes, Φ FL was also found to decrease for substituted-carbohelicenes with increase in chain length. , Halogenation of carbohelicene rings is another strategy to tune the chiroptical properties. , Synthesis of various fluorinated carbohelicenes are reported in the literature. ,,, In the work of Nakai et al, a systematic improvement in CD intensities of the 1 B b band was observed along with their corresponding dissymmetry factors, after substitutions by F, Cl, and Br atoms. This was attributed to increase in | μ | and | m |, and a small angle between the two vectors.…”
Section: Introductionmentioning
confidence: 99%
“…The new systems were designed such as to keep the D 2 symmetry intact. It is worth mentioning that fluorination of the backbone of carbon‐based materials has been a very good strategy to alter the optical properties [17–22] . Substitutions by fluorine atoms affect the crystal structures by inducing C−H⋅⋅⋅−F interactions [17–22] .…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that fluorination of the backbone of carbon-based materials has been a very good strategy to alter the optical properties. [17][18][19][20][21][22] Substitutions by fluorine atoms affect the crystal structures by inducing CÀ H•••À F interactions. [17][18][19][20][21][22] In this work, using computational tools, the chiroptical properties are calculated for all the six systems and the results for the fluorinated compounds are compared against those of 5HD.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, organic semiconductor materials have attracted extensive research interest because of their great advantages in terms of definite molecular structure, easy purification, flexibility, low cost, and so forth. It is well known that the carrier mobility largely depends on the intermolecular stacking style in fabricated films. Large amounts of small molecules have been designed and synthesized to discuss the effects of molecular planarity, conjugated length, distortion of the conjugate skeleton, flexible side-chain length, and different heteroatom groups on the intermolecular stacking; this molecular structure innovation is always looked as a comprehensive and complex task with a long-term synthesis process and is laborious. Therefore, various thin-film postprocessing techniques such as thermal annealing (TA) have been studied to improve the intermolecular stacking, which is considered as a simple and effective method, but TA is blind to promote the ordered arrangement of molecules and cannot guide molecules to form a desired stacking mode according to the characteristics of the molecular structure. Recently, the solvent vapor annealing (SVA) technique has been tried to be used in the preparation of organic photovoltaic devices and field-effect transistor devices to carry out thin-ilm post-processing to improve the molecular alignment state, which can select a suitable solvent for the molecular structure to induce the desired molecular alignment. …”
Section: Introductionmentioning
confidence: 99%